2005
DOI: 10.1007/s00127-005-0939-5
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psychiatric disorders among 5–10 year olds in rural, urban and slum areas in Bangladesh

Abstract: A conservative extrapolation is that around 5 million Bangladeshi children and adolescents have psychiatric disorders. In a country with very few child mental health professionals, there is a vast gap between need and provision that must be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
121
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 22 publications
16
121
3
3
Order By: Relevance
“…The present study revealed a statistically significant relationship between OCD and the religious practice of the patients (Table 5); this can be explained by overall religious practices and beliefs of Bangladeshi people. Moreover, similar results were found in another study that assessed the relationship between OCD symptoms and religious practice (1,8).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present study revealed a statistically significant relationship between OCD and the religious practice of the patients (Table 5); this can be explained by overall religious practices and beliefs of Bangladeshi people. Moreover, similar results were found in another study that assessed the relationship between OCD symptoms and religious practice (1,8).…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, comorbidity is also higher in children and adolescents with OCD, and 80% of the patients may meet the diagnostic criteria for another mental health disorder such as anxiety disorder, depressive disorder, attention deficit disorder, oppositional defiant disorder (ODD), conduct disorder (CD), or tic disorder because as many as 50% to 60% of youths experience two or more other mental disorders during their lifetime (1,2,(5)(6)(7). Epidemiological studies indicate that the prevalence of OCD in children and adolescents is 2% in Bangladesh, and this finding is in line with studies conducted in different cultures with variations in presentations of symptoms (1,8). The presentation of OCD symptoms in children and adolescents in Bangladesh is yet to be studied.…”
Section: Introductionsupporting
confidence: 67%
“…In part, this is due to the sheer physical difficulty of entering such areas, and finding co-operative adults to interview. Available studies suggest that mental and physical health of children and adolescents in such areas is significantly worse than in both rural and stable urban dwellers (Mullick and Goodman 2005;). Almost certainly, the disadvantages experienced by girls and women in rural areas pertain in urban slums, probably to a greater extent than in any other part of Bangladeshi society .…”
Section: Rural-to-urban Migrationmentioning
confidence: 99%
“…Two studies conducted in Bangladesh on general child and adolescent population found overall prevalence of psychiatric disorder 15.2% and 18.4% (Mullick & Goodman, 2005;Rabbani et al, 2009). The present study found that overall prevalence of psychiatric disorder in female respondents was 93.0%.…”
Section: Discussionmentioning
confidence: 99%
“…DAWBA is an internationally well accepted research instrument and a novel package of questionnaires, interviews, and rating techniques designed to generate ICD-10 psychiatric diagnoses among children and adolescents of 5 to 16 years (extended up to 18 years) (Goodman et al, 2000). This instrument has been translated in B angla and standardized and validated by Mullick & Goodman (2005). DAWBA has three versions-parent version, self version and teacher version.…”
Section: Methodsmentioning
confidence: 99%